OPTIMIZATION OF SMALL FISHERIES ENTERPRISE WITH FISHERY PERFORMANCE INDICATORS THROUGH TRIPLE BOTTOM LINE - Maulana, Danis; Wati, Merlin Dyah; Agatha Putri, Mirza Safitri (Jurnal Entrepreneur dan Entrepreneurship, 2017)
The development of micro, small and medium enterprises (MSMEs) in Indonesia underwent an increasing trend from 2013 to the end of 2014. This was evidenced by self-reliant SMEs whose main economic activities were in the macro sector. Inversely, MSMEs’ fisheries sector only contributed 3.25% to GDP in 2014. The assessment of macro fishery performance system can be measured through Fishery Performance Indicators method as introduced by James L. Anderson and Christopher M. Their export assessment method is based on input and output factors reflecting success in achieving sustainability. By knowing the size of the export, Small Fisheries Enterprise can maximize the aspects needed in optimizing the process from upstream to downstream using Triple Bottom Line method. This method is implemented based on three measures of economic, social, and environmental performance. They measure business success not only in terms of financial perspective but also economic perspective by optimizing the National Fish Logistics System broadly and involving communities and environments.